Reversible renal failure due to psychogenic urinary retention. Issue 715 (May 1985) - Korzets, Z.; Garb, R.; Lewis, S.; Bernheim, J. L.
Abstract : A case of advanced, reversible renal failure due to psychogenic urinary retention occurring in a 17 year old female, is reported. The diagnosis of psychogenic urinary retention was made on the basis of existent florid psychopathology and the concomitant exclusion of an organic cause. Family psychodynamics are discussed. Psychosocial intervention led to a resumption of normal micturition, the disappearance of the urinary retention with resultant improvement of renal function.